A Travel Point-of-Interest Recommendation Algorithm Incorporating Social Features and Logistic Matrix Factorisation - Wang, Qian; Wei, Jiayin; Yao, Lin; Lu, Youjun; Feng, Fujian; Peng, Dan (Computing and Informatics, 2026)
With the growing demand for personalised travel experiences, the development and application of travel point-of-interest (POI) recommendation systems have become increasingly important. However, many existing systems often underperform owing to insufficient integration of social features and contextual information. To address this issue, the S-LMF algorithm is proposed, combining social features with logistic matrix factorisation to improve recommendation accuracy. This approach simulates social influence by incorporating joint check-in similarity and friendship factors, while logistic matrix factorisation leverages check-in frequency data to refine POI recommendations. The effectiveness of social features and logistic matrix factorisation (S-LMF) was tested against five baseline algorithms using publicly available data sets from Yelp and Gowalla. Results demonstrated that S-LMF outperformed the best baseline model by improving Precision@20 by 22.95% on Yelp and 28.60% on Gowalla. Moreover, it increased Recall@10 by 17.95% on Yelp and 8.19% on Gowalla.